PENDAMPINGAN SENAM LANSIA DI DESA KOLOR KABUPATEN SUMENEP - Sri Sumarni; Laylatul Hasanah (LPPM Universitas Bina Bangsa, 2022)
Gymnastics for the elderly is a light exercise that is easy to do, not burdensome which is applied to the elderly. This sports activity will help the body to stay fit and fresh because it trains bones to stay strong, encourages the heart to work optimally and helps eliminate free radicals that roam in the body. So elderly gymnastics is a series of tone movements that are regular and directed and planned which are followed by elderly people which are carried out with the aim of increasing the functional ability of the body to achieve these goals. The coverage of elderly gymnastics in Kolor Village only reached 45%. So the problem of elderly gymnastics in Kolor Village, City District. One solution to this problem is the need for an understanding of the 10 Laporan Akhir PKM Universitas Wiraraja elderly that elderly exercise is very important in physical and spiritual health. The place or location for PKM activities is carried out in Kolor Village, Kota Subdistrict which will be held in June-August 2021, the PKM target group is Elderly Citizens